Dynamic Impedance Distribution of Nanoscale Electrodes: Fabrication and Characterization - S. Dhahi, Thikra (Micro and Nanosystems, 2015)
Nanogap electrodes fabricated from metals separated by a distance on nanometer scale have gained tremendous acceptance in various fields of applications and essential elements of nanoscale biosensor transducers and electrochemical sensing element. Electrical conduction of nanogap is typically deternimed by the characteristics of its electron transport molecules and mainly conducted through current-voltage (I-V) measurements. However, due to capacitively shifting behavior of the nanogap device as a result of atomic agintation by the increase in frequency, it is difficult to measure two devices of the same configuration that produce exact behavior. In order to understand these fundamentals, three gap electrodes of three different materials were fabricated and tested for their impedance behavior to identify sensitive and stable atomic configuration mode for maximum detection throughput.
Keywords: silicon